2012
DOI: 10.1002/gps.3893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a standardized humor group in a clinical setting: a feasibility study for older patients with depression

Abstract: Our results indicate an additional benefit of this specific therapeutic intervention for older depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
2
49
1
9
Order By: Relevance
“…Nevertheless, we found short-term effects for depression in this study. This is in line with findings for humor-based programs that were also effective in depressed patients (e.g., Falkenberg, Buchkremer, Bartels, & Wild, 2011;Konradt et al, 2013). Overall, results for the replication of the findings for the three funny things-intervention were mixed, as we could replicate the ameliorating effects on depressive symptoms only in the short-term (findings for happiness were replicated though).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, we found short-term effects for depression in this study. This is in line with findings for humor-based programs that were also effective in depressed patients (e.g., Falkenberg, Buchkremer, Bartels, & Wild, 2011;Konradt et al, 2013). Overall, results for the replication of the findings for the three funny things-intervention were mixed, as we could replicate the ameliorating effects on depressive symptoms only in the short-term (findings for happiness were replicated though).…”
Section: Discussionsupporting
confidence: 82%
“…Vaillant (e.g., 2000) has argued that humor may contribute to healthy aging (as a mature defense mechanism). There are also humor-based programs in the elderly that are effective in ameliorating depression, anxiety, or pain (e.g., Ganz & Jacobs, 2014;Hirsch, Junglas, Konradt, & Jonitz, 2010;Konradt, Hirsch, Jonitz, & Junglas, 2013;Low et al, 2013; for an overview see Ruch & McGhee, 2014), or in enhancing positive affect in habitants of residential homes (Houston, McKee, Carroll, & Marsh, 1998). Humor is also potent in inducing the positive emotion of amusement (Ruch, 2001(Ruch, , 2009, which may be helpful in the building of resources for well-being (Fredrickson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the economy in the presentation and conduct of the study is a plus for this type of interventions. However, it needs to be acknowledged that individually conducted interventions and those that are conducted with groups could POSITIVE INTERVENTIONS IN PEOPLE AGED 50-79 YEARS 17 be more effective (Sin & Lyubomirsky, 2009 However, findings from other research groups (e.g., Hirsch et al, 2010;Konradt et al, 2013;Ramírez et al, 2013) are encouraging. The question arises on the suitability of the current design for clinical populations.…”
Section: Positive Interventions In People Aged 50-79 Years 15mentioning
confidence: 99%
“…It was suggested that humor plays an important role for the well-being of older adults (e.g., Konradt, Hirsch, Jonitz, & Junglas, 2013;Proyer, Ruch, & Müller, 2010;Ruch & McGhee, in press;Ruch, Proyer, & Weber, 2010b). Konradt et al (2013) tested the effects of a standardized humor therapy group for depressive patients (compared to a group of patients with no treatment); all ≥ 61 years of age. Only patients in the humorgroup showed lower state seriousness and greater satisfaction with life after completion of the program (see also Hirsch, Junglas, Konradt, & Jonitz, 2010).…”
mentioning
confidence: 99%
“…Preliminary results indicate that it may be important to choose “healthy” styles of humor that promote positive affect, and that results should be closely monitored 79. It also should be noted that humor is being used as part of psychotherapy, for example in the management of depression 95,96. However, it is not clear whether the humor used needs to be condition-specific.…”
Section: Humor—a Tool For Copingmentioning
confidence: 99%